2009
DOI: 10.1111/j.1467-789x.2009.00662.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of melanocortin neuronal pathways in circadian biology: a new homeostatic output involving melanocortin‐3 receptors?

Abstract: Obesity, insulin resistance and increased propensity for type 2 diabetes and cardiovascular disease result from an imbalance between energy intake and expenditure. The cloning of genes involved in energy homeostasis produced a simple feedback model for the homeostatic regulation of adipose mass. Serum leptin secreted from adipocytes signals nutrient sufficiency, curbing appetite and supporting energy expenditure. A rapid decline in leptin during nutrient scarcity instigates adaptive mechanisms, including incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 116 publications
0
17
0
Order By: Relevance
“…The MC3-R −/− mouse is resistant to the induction of natriuresis by γ-MSH, is sensitive to hypertension induced by a high-salt diet, and displays defects in circadian rhythms (17,18). During the course of our studies on obesity in the MC3-R −/− mouse, we found that, although lipogenesis appeared normal, fasting-induced mobilization of fatty acids from adipose tissue was blunted.…”
mentioning
confidence: 78%
“…The MC3-R −/− mouse is resistant to the induction of natriuresis by γ-MSH, is sensitive to hypertension induced by a high-salt diet, and displays defects in circadian rhythms (17,18). During the course of our studies on obesity in the MC3-R −/− mouse, we found that, although lipogenesis appeared normal, fasting-induced mobilization of fatty acids from adipose tissue was blunted.…”
mentioning
confidence: 78%
“…43 Furthermore, the ability to synchronize rhythms of increased vigilance and food-seeking behaviours that anticipate nutrient GPCRs in energy homeostasis/balance N Gallo-Payet consumption requires functional MC3R. 15,16,18,43,44 The results from Begriche et al 15,16,45 suggest that MC3Rs modulate the expression of the 'anticipatory' response to nutrients. Mc3r À/À mice subjected to daily RF regimes in which 60--70% of normal caloric intake is presented mid-light cycle or at 24-h intervals in constant dark exhibit attenuated 'food anticipatory activity'.…”
mentioning
confidence: 92%
“…39--41 The laboratory of Andrew Butler has focused on a role for MC3R in the expression of circadian rhythms in anticipatory behaviour. 15,16,42 Restricted feeding (RF) paradigms with a periodicity of 24 h rapidly induce entrainment of rhythms anticipating food presentation that are independent of master clocks in the suprachiasmatic nucleus but do require other hypothalamic structures. Sutton et al 43 reported that the melanocortin system is required for the expression of food-entrainable rhythms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More consistently, however, Mc3r −/− mice show greater feeding efficiency (the ratio of weight gain to energy intake) [36]. They have also been reported to have decreased locomotor activity particularly during the dark phase [41] and altered circadian rhythmicity in constant dark conditions [42]. They are, under most conditions hypophagic or normophagic relative to controls and appear to maintain normal metabolic rate and metabolic profiles despite their obese phenotype.…”
Section: Introductionmentioning
confidence: 99%